mRNA vaccine trafficking and resulting protein expression after intramuscular administration - Kimberly J. Hassett; Ivana Liric Rajlic; Kapil Bahl; Rebecca White; Kristen Cowens; Eric Jacquinet; Kristine E. Burke (Elsevier, 2024)
The mRNA vaccine route from injection site to critical immunologic tissues, as well as the localization of protein antigen following intramuscular (i.m.) administration, is crucial to generating an effective immune response. Here, we quantified mRNA at the injection site, lymph nodes, and in select tissues. mRNA was primarily present 24 h after administration and then rapidly degraded from local and systemic tissues. Histological analyses of mRNA and expressed protein at the site of administration and in the lymph nodes following i.m. administration of our vaccine in rodents and nonhuman primates (NHPs) were completed, and mRNA and protein expression were detected in tissue resident and infiltrating immune cells at the injection site. In addition, high levels of protein expression were observed within subcapsular and medullary sinus macrophages in draining lymph nodes. More important, results were similar between rodents and NHPs, indicating cross-species similarities.